Kedudukan Alkitab Bagi Kurikulum Di Era Revolusi Industri 4.0 Bagi Orang Dewasa - Ottovianus Otto (JURNAL LUXNOS, 2019)
Abstract: This paper aims to see how the Bible stands for the curriculum in the era of the industrial revolution 4.0 called the Internet of Think (IoT). Internet of Think (IoT) is a technology that allows each instrument to be connected to one another virtually, so that it can support the performance of the human workforce. Therefore, with the development of the 4.0 industrial revolution, this paper will explain how the authority of the Bible and the relevance of the Bible, the benefits of God's words based on II Timothy 3:16 (teaching, reproving mistakes, correcting behavior and educating people in truth) and the position of the Bible for curriculum in the era of the industrial revolution 4.0. Abstrak: Tulisan ini bertujuan untuk melihat bagaimana kedudukan Alkitab bagi kurikulum di era revolusi industri 4.0 yang disebut Internet of Think (IoT). Internet of Think (IoT) merupakan teknologi yang memungkinkan setiap instrumen terkoneksi satu sama lain secara virtual, sehingga mampu mendukung kinerja tenaga kerja manusia. Oleh karena itu, dengan adanya perkembangan revolusi industri 4.0 maka, tulisan ini akan menjelaskan bagaimana otoritas Alkitab dan relevansi Alkitab, manfaat perkataan Allah berdasarkan II Timotius 3:16 (mengajar, menyatakan kesalahan, memperbaiki kelakuan dan mendidik orang dalam kebenaran) dan kedudukan Alkitab bagi kurikulum di era revolusi industri 4.0.